EVALUASI PENGENDALIAN INTERNAL SISTEM INFORMASI AKUNTANSI ATAS SIKLUS PENJUALAN DAN PENERIMAAN KAS (Studi Kasus pada PT GEOFF MAKSIMAL JAYA) - Alya Tasqiya Khumaira (Jurnal Proaksi, 2021)
This study aims to examine and find about implementation of internal control evaluation of Accounting Information Systems (Case Study at PT Geoff Maksimal Jaya. Sales and cash receipts are one of the most important components for a company and are very easy to abuse. The purpose of this study is to evaluate the weaknesses and strengths of the internal control system of the accounting information system on cash receipts for the sales cycle at PT Geoff Maximal Jaya. This research is a qualitative research using an evaluation program by comparing it with internal control based on COSO theory. The results of this study are the internal control of cash receipts over the sales cycle is quite good, but there are still aspects that are not in accordance with COSO theory, namely the merger between the sales function and the credit function. Keywords: Internal Control, Sales and Cash Receipt Cycle, COSO